On the difference equation of higher order - Çinar, Cengiz; Mansour, Toufik; Yalçinkaya, Ibrahim (Utilitas Mathematica, 2013)
In this paper, we investigate the global behavior of the difference equation xn+1 = a + 1/√aα-1xnxn-kα/xn + 1/√aα-1xn-kα, n = 0, 1, ... where k is a positive integer, a, α ε (0, ∞) and x0, x-1, ..., x-k > 0.